Changes in TNF and IL-6 production after diphtheria toxoid vaccination: drug modulation of the cytokine levels - A. L. Pukhalsky; M. S. Bliacher; A. V. Danilina; E. A. Kalashnikova; T. K. Lopatina; I. M. Fedorova (Hindawi Limited, 1996)
The effect of vaccination with diphtheria toxoid (AD-M) on TNF and IL-6 production has been studied in humans. In the present study it was demonstrated that immunization with AD-M resulted in changes of in vitro TNF and IL-6 production by peripheral blood mononuclear cells. TNF release was suppressed but IL-6 production was stimulated. On the other hand, serum levels of TNF were markedly increased over a period of 3 weeks. It was also demonstrated that the postvaccinal cytokine production disturbances may be corrected by pretreatment with a new synthetic hexapeptid (Imunofan®). It is possible that the imunofan treatment could prevent some postvaccinal complications.